Effects of different media and nitrogen sources and levels on growth and lipid of green microalga Botryococcus braunii KMITL and its biodiesel properties based on fatty acid composition - Ruangsomboon, Suneerat (My University, 2015)
This work aimed to find an optimum culture medium for green microalga Botryococcus braunii KMITL and investigate its biodiesel properties based on fatty acid composition. Four different media were tested. Chlorella medium was the best medium for lipid yield. Among four nitrogen sources tested, KNO3 produced the highest lipid yield. When varied the nitrogen concentrations, this strain gave the highest lipid yield at the highest nitrogen level. When cultivated in the best medium and nitrogen source and level for 30 days, and then cultivated further for 14 days in the medium with no nitrogen, the highest lipid content and yield were 49.94 ± 0.82% and 2.71 ± 0.02 g L-1, respectively. C16:0 fatty acid was the major fatty acid found. Fatty acid profiles of B. braunii KMITL cultivated in Chlorella medium with 1.25 g L-1 KNO3 gave the best biodiesel properties with the lowest iodine value, maximum cetane number, and lowest degree of unsaturation.
Keywords: Biodiesel; Cetane; Chlorella medium; Fatty acid; Lipid productivity